2014
DOI: 10.1007/s10484-014-9267-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neurofeedback Training on Depression and Fatigue in Patients with Multiple Sclerosis

Abstract: Depression and fatigue are common symptoms of multiple sclerosis (MS) and are the primary determinants of impaired quality of life in this demyelinating neurological disease. Untreated depression is associated with suicidal ideation, impaired cognitive function and poor adherence to immunomodulatory treatment. For these reasons, systematic screening and management of depressive symptoms and fatigue is recommended for all patients with MS. The objective of this study was to evaluate the effectiveness of neurofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…The findings from this case series provide additional evidence suggesting that neurofeedback might be an effective method for helping some (and perhaps many) individuals with chronic pain learn self-management skills that would give them more control over, and alleviate, their suffering, and also result in improvements in other related symptoms and problems. This latter point is supported by the findings of Choobforoushzadeh, Neshat-Doost, Molavi, and Abedi (2015), who found that neurofeedback reduced symptoms of depression and fatigue in patients with multiple sclerosis. More research is also warranted to evaluate the efficacy of neurofeedback, relative to other pain treatments, to distinguish the specific from the nonspecific effects of neurofeedback, and to identify the training protocols that are most effective for patients with different pain conditions.…”
Section: Discussionsupporting
confidence: 58%
“…The findings from this case series provide additional evidence suggesting that neurofeedback might be an effective method for helping some (and perhaps many) individuals with chronic pain learn self-management skills that would give them more control over, and alleviate, their suffering, and also result in improvements in other related symptoms and problems. This latter point is supported by the findings of Choobforoushzadeh, Neshat-Doost, Molavi, and Abedi (2015), who found that neurofeedback reduced symptoms of depression and fatigue in patients with multiple sclerosis. More research is also warranted to evaluate the efficacy of neurofeedback, relative to other pain treatments, to distinguish the specific from the nonspecific effects of neurofeedback, and to identify the training protocols that are most effective for patients with different pain conditions.…”
Section: Discussionsupporting
confidence: 58%
“…According to the investigation and the data obtained from the questionnaire, these results were as follows: EEG feedback therapy on quality of life in patients with multiple sclerosis in post-test and follow up Phase was effective. These findings indirectly coordinated with Choobforoushzadeh et al [19], Pampa Reddy et al [20], Hammond [21], Hammond [22]. Several studies regarding the effectiveness of EEG feedback therapy was conducted on patients with MS.…”
Section: Discussionsupporting
confidence: 67%
“…Among their 20 participants with MDD, 15% and 55% had remission of their condition at 4 weeks and 8 weeks, respectively. In a study of 24 people with multiple sclerosis who had significant depression and fatigue, Choobforoushzadeh, Neshat-Doost, Molavi, and Abedi (2015) provided half of participants with neurofeedback and the other half with "treatment as usual." Their neurofeedback protocol consisted of down-training theta and alpha waves, and up-training first beta and then SMR, at F3.…”
Section: Neurofeedback Trainingmentioning
confidence: 99%